JOURNEY TO EQUALITY IN AUGUST WILSON’S PLAY SCRIPT RADIO GOLF (2005) - Miki Roma Putra; Kurnia Ningsih; An Fauzia Rozani Syafe’i (Universitas Negeri Padang, 2018)
The purpose of this analysis is to expose the issue about journey to equality which is done by Black American and to know the contribution of the plot, setting, and character in revealing the journey to equality. This analysis is related to the concept double-consciousnessby W.E.B. Du Bois that is supported by the text and context based interpretation. The result of this analysis shows Black American do efforts to get the equality that can be seen from their efforts to build good images and careers and works.